Reka Bentuk Tiny House Berunsurkan Elemen Hijau Mampu Milik - Abdillah, Muhammad Afiq Imran; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2023)
A tiny house is an affordable house concept for low-income people according to their budget and taste. One of the biggest problems facing low-income households today is finding an affordable, safe and comfortable home. Tiny house builders spend high costs depending on the choice or supply of materials. Therefore, the objective of this study is to identify the design tastes that are often in demand for the construction of tiny houses based on green elements, identify flexible cost items for the construction of tiny houses based on green elements and design tiny house buildings based on green elements by taking consider popular design tastes and flexible costs. The scope of this study involved 105 buyer respondents and 8 tiny house contractor respondents based on green elements around the Kuala Terengganu area. This study uses a mixed approach that is quantitative, qualitative and the use of computer software by conducting a questionnaire with tiny house buyers, interviewing contractors in Kuala Terengganu as well as coding tiny house floor plan data. Data analysis using descriptive statistical methods (mean and score), content and comparison matrix and Revit application design. The results of the study from the responses of 105 respondents equal to 30% and 8 respondents interviewed found that the design criteria that buyers are most interested in are the green building environment and Mognolia V7 design. The most flexible cost item for the construction of a tiny house based on green elements is the operating cost. The design of the floor plan of the house that needs to be adapted is based on the aspect of energy saving. In conclusion, this study can help the parties involved to get realistic ideas in designing a tiny house based on green elements and able to satisfy the tastes of buyers who can afford it.